Reflections on Associative Word Links in Judges - Kaminsky, Joel S. 1960- (2012)
Attempts to read Judges in a unified fashion have shed much light on this book. Yet, such readings often are not fully convincing because they gloss over details that do not easily fit into the literary, theological, or ideological perspective being advanced. This essay moves in a new direction by exploring a thick web of verbal resonances that brings various distinct components within Judges into a complex literary and theological conversation. Even as this webbing draws various parts of the book into association with each other, it at the same time highlights the distinct elements of each story. While many narratives in Judges are indeed interconnected, it is less clear that Judges contains a linear and progressive narrative with an over-arching message.
Keywords: Bibel; Bibel; Bibel; Wortspiel; Semantik; Erzähltheorie; literary approaches to the Bible; Narrative Theology; verbal wordplay; inter-textual allusion; Judges